Performance Efficiency of the Zeolite Synthesized from Fly Ash in Wastewater Treatment - B, Subramanyam; Gunjalli, Gowthami; S, Aishwarya; Priya M, Charu (International Journal of Engineering and Technology, 2018)
In the present study we are exploring the possibility of using fly ash to produce zeolite. In this synthesis process, class F fly ash from Neyveli Thermal Power Plant, Cuddalore district, Tamil Nadu, India was utilized. The fly ash was subjected to fusion process with sodium hydroxide for an hour. The synthesized material was characterized to obtain the mineral composition. The resulting zeolite is competitive with commercially available materials which are used as ion exchangers in wastewater treatment and soil decontamination. In this study, the synthesized zeolite was analyzed for the performance removal efficiency of pollutants from domestic wastewater. The batch method was adopted to study the influential parameters, such as initial pH value of the solution, and dosage of zeolite, in the domestic wastewater treatment process.Â Â Â